Hypogean pseudoscorpions (Arachnida) from Jaén province (Andalusia, Spain), with descriptions of four new species and a new synonymy - Zaragoza, Juan A.; Pérez, Toni (Zootaxa, 2013)
Four new hypogean species are described from the Jaén province (southern Spain): Chthonius (Ephippiochthonius) espanyoli sp. nov., C. (E.) giennensis sp. nov., C. (E.) villacarrillo sp. nov. and Neobisium (Ommatoblothrus) perezruizi sp. nov. New records are given for the species Chthonius (E.) cazorlensis, C. (E.) perezi, C. (E.) tetrachelatus, Neobisium (O.) perezi, Microcreagrella caeca caeca and Allochernes masi. Chthonius (E.) verai and C. (E.) minutus are removed from the list of the Andalusian fauna. A new synonymy is proposed: Neobisium (O.) gev Carabajal Márquez, García Carrillo & Rodríguez Fernández, 2011, is a junior subjective synonym of N. (O.) perezi Carabajal Márquez, García Carrillo & Rodríguez Fernández, 2011.